การวิเคราะห์องค์ประกอบเชิงยืนยันของการนำปรัชญาเศรษฐกิจพอเพียง ไปใช้ในการจัดการการท่องเที่ยวชุมชน: Confirmatory Factor Analysis of Management of Tourism Community Model based on Sufficiency Economy Philosophy in Nakornnayok Province - Patcharin Jungpraat , พัชรินทร์ จึงประวัติ; Matura Suansri , มธุรา สวนศรี; Pimpika Thongrom, พิมพิกา ทองรมย์ (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2023)
The objectives of the research were 1) to study the potential of tourism villages in Nakhon Nayok; and 2) Confirmatory Factor Analysis of the Management of the Tourism Community Model based on the Sufficiency Economy Philosophy in Nakornnayok Province. The methodology was a mixed method using the semi-structured interview and the questionnaire survey. The number of 60 interviewees were selected by purposive sampling. They were the head of the village who involve in tourism activities following the application of the Sufficiency Economy Philosophy. The questionnaire was distributed using the random number table of the house number in the village of Wat Fung Klong village, Koh Wai SubDistrict, Pak Pli District, Nakhon Nayok Province, and Tung Kraprong village, Pa Kha Sub-District, Banna District, Nakhon Nayok Province. A total number of 140 questionnaires were completed. The data was analyzed using descriptive statistics such as frequency, percentage, mean, standard deviation, and Pearson correlation. The data was further analyzed using the second-order confirmation. The results found that the Wat Fung Klong village and Tung Kraprong village village have the potential to develop the application of the efficiency economic philosophy in community-based tourism management. As a result of the availability of natural resources, a culture, a way of life, and wisdom can be developed into a local tourist attraction. The local populace is also prepared to participate in tourism management. The outcomes of individual-level second order confirmatory factor analysis data analysis. The ideology of the sufficiency economy places great importance on managing community tourism, which is given greater weight than social class. The most minor sub-component is my involvement in the transformation of the area into a destination that could attract tourists. The component weights for the societal level were quite similar to those for the individual level. This results from the fact that my community provides a range of Sufficiency Economy–aligned activities.